Merawat Kerukunan di Desa Cikawungading, Kecamatan Cipatujah, Kabupaten Tasikmalaya, Jawa Barat - Miharja, Deni; Hernawan, Wawan (Religió: Jurnal Studi Agama-agama, 2017)
There is a relationship among religion, social and environmental conditions as a place of settlement of a society. This is a hypothesis of caring for harmony in Cikawungading Village. Through this hypothesis, the social environment has a significant influence on the form of the relationship. The process of social transformation is possible so that needed to maintain harmony, because in this village there were attacks and burning on 36 houses, 2 churches and a wood processing factory, with a total of 181 refugees. The focus of this study is to find out the characteristics of the Cikawungading Village community's diversity and the efforts that must be carried out by government agencies, institutions under the Ministry of Religion, and Universities in providing assistance and understanding about the importance of harmonious living in the conditions of pluralistic and multi-religious communities. To answer this problem, researchers used Quintan Wiktorowicz's social movement theory with a multidisciplinary approaches. The results showed, firstly, the community in Cikawungading village have now lived in harmony with each other. They have accustomed to mutual understanding in worship, giving each other help, and not disturbing each other. Secondly, the concern of government agencies, institutions under the Ministry of Religion, and Higher Education is expected to be present in their midst. The expected form of attendance is the training, especially in the momentum of religious holidays and activities to increase community income.   [Hubungan antara agama dengan kondisi sosial dan lingkungan sebagai tempat bermukimnya suatu masyarakat merupakan hipotesis dari merawat kerukunan di Desa Cikawungading. Melalui hipotesis ini, penelitian lingkungan sosial memiliki pengaruh signifikan terhadap bentuk hubungan tersebut. Proses transformasi sosial dimungkinkan terjadi sehingga perlu merawat kerukunan, karena di desa ini pada tahun 2001 telah terjadi penyerangan dan pembakaran terhadap 36 rumah penduduk, 2 gereja, dan sebuah pabrik pengolahan kayu, dengan jumlah pengungsi secara keseluruhan mencapai 181 jiwa. Fokus dari kajian ini adalah ingin mengetahui karakteristik keberagamaan masyarakat Desa Cikawungading dan upaya yang harus dilakukan instansi pemerintah, lembaga-lembaga di bawah Kementerian Agama, maupun Perguruan Tinggi dalam melakukan pendampingan dan pemberian pemahaman tentang pentingnya hidup rukun dalam kondisi masyarakat yang majemuk dan multi religi. Untuk menjawab masalah tersebut, peneliti menggunakan teori gerakan sosial dari Quintan Wiktorowicz dengan pendekatan multidisipliner. Hasil penelitian menunjukkan, pertama, masyarakat di Desa Cikawungading kini telah hidup rukun satu dengan lainnya. Mereka sudah terbiasa saling pengertian dalam ibadah, saling memberi bantuan, serta tidak saling mengganggu. Kedua, kepedulian instansi pemerintah, lembaga-lembaga di bawah Kementerian Agama, maupun Perguruan Tinggi sangat diharapkan untuk hadir di tengah-tengah mereka. Bentuk kehadiran yang diharapkan, terutama dalam momentum kegiatan Peringatan Hari Besar Keagamaan dan kegiatan peningkatan pendapatan masyarakat adalah melalui pelatihan.